Early Clinically Relevant Improvement in Quality of Life and Clinical Outcomes 1 Year Postsurgery in Patients with Knee and Hip Joint Arthroplasties. (April 2018) - Neuprez, Audrey; Neuprez, Arnaud H.; Kaux, Jean-François; Kurth, William; Daniel, Christophe; Thirion, Thierry; Huskin, Jean-Pierre; Gillet, Philippe; Bruyère, Olivier; Reginster, Jean-Yves
Objective: To measure and identify the determinants of the outcomes after hip/knee arthroplasty (HA/KA) in patients with osteoarthritis during the first postsurgical year. Design: In this prospective observational study, we evaluated the preoperative and postoperative (3, 6, and 12 months) outcomes of 626 patients who underwent HA (346 with median age 65 years, 59% female) or KA (280 with median age 66.5 years, 54% female) between 2008 and 2013. Generic and specific tools were used to measure health-related quality of life (HRQoL) and utility. Good outcome was defined as an improvement in WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) greater than or equal to the minimal important difference (MID). Regressions were performed to evaluate the relationship between preoperative and postoperative measures and evolution of WOMAC/good outcome. Results: We observed an almost systematic improvement of all parameters for up to 12 months, but especially at the 3-month follow-up. The low number of comorbidities and the absence of postoperative complications were the common determinants of improvement of WOMAC total score after 12 months. Other parameters (background of the joint, preoperative function and length of hospital stay in KA group; place of discharge in HA group) affected the evolution of WOMAC scores. 87.09% of HA and 73.06% of KA patients experienced a good outcome. A small number of comorbidities, a worse preoperative function, a shortened hospital stay (KA only), and an absence of early postoperative complications (HA only) significantly predicted a good outcome. Conclusions: Intermediate HRQoL following HA or KA improved quickly from preoperative levels for all instruments. More than 70% of patients achieved a good outcome defined as improved pain, stiffness and disability and the predictors are slightly close.